Long-term follow up of families with pathogenic NFKB1 variants reveals incomplete penetrance and frequent inflammatory sequelae - Tuovinen, Elina A.; Kuismin, Outi; Soikkonen, Leila; Martelius, Timi; Kaustio, Meri; Hämäläinen, Sari; Viskari, Hanna; Syrjänen, Jaana; Wartiovaara-Kautto, Ulla; Eklund, Kari K.; Saarela, Janna; Varjosalo, Markku; et al. (Clinical immunology (Orlando, Fla.), 2023)
Nuclear factor κ light-chain enhancer of activated B cells (NF-κB) family of evolutionarily conserved transcription factors are involved in key cellular signaling pathways. Previously, hypogammaglobulinemia and common variable immunodeficiency (CVID)-like phenotypes have been associated with NFKB1 variants and loss-of-function NFKB1 variants have been reported as the most common monogenic cause for CVID among Europeans. Here, we describe a Finnish cohort of NFKB1 carriers consisting of 31 living subjects in six different families carrying five distinct heterozygous variants. In contrast to previous reports, the clinical penetrance was not complete even with advancing age and the prevalence of CVID/hypogammaglobulinemia was significantly lower, whereas (auto)inflammatory manifestations were more common (42% of the total cohort). At current stage of knowledge, routine genetic screening of asymptomatic individuals is not recommended, but counseling of potential adult carriers seems necessary. •Penetrance of NFKB1 haploinsufficiency is incomplete in screened families.•Inflammatory complications are more common than symptomatic antibody deficiency.•Routine genetic screening of all potential carriers is not recommended.•Genetic counseling of adult carriers and their parents seems imperative.